THE HYPERMASCULINITY AS SEEN IN THE MAIN CHARACTER IN RAMBO: LAST BLOOD MOVIE - Ria Marina Nababan; Ely Nurmaily (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2021)
This paper revealed the practice of hypermasculinity through the main character which is Rambo. Therefore, the aims of the writer is to make the reader can see and know the part of themselves in a good way, be a useful person for others, and respects the live of others. In conducting this research, the writer uses a qualitative method since the writer wanted to have an in-depth analysis of the data and Rambo: Last Blood Movie as the source of the data to do the analysis. This research was library research in which the writer acquire the informations by finding relevant journals, books, and visiting reliable websites. The writer uses the theory by Ankita Siddhanta about hypermasculinity in analyzing the data. The finding of this current study shows that there are some characteristics and actions which can be categorized as the practice of hypermasculinity based on the dialogues, scenes, actions of Rambo’s character in the movie.Keywords: Hypermasculinity, rambo, rambo: Last Blood Movie, the writer.